Modeling Downward Groundwater Leakage Rate to Evaluate the Relative Probability of Sinkhole Development at an Under-Construction Expressway and Its Vicinity - Xiao, Han; Li, Haiming (Frontiers in Earth Science, 2020)
Sinkhole development has been recognized as a major geohazard, as sinkholes pose great threats to infrastructure, such as buildings, roads, bridges, and pipelines, resulting in huge financial losses to society. Previous studies indicated that the spatial density of sinkholes increases linearly with the downward groundwater leakage rate (DGLR) (inter-aquifer flow rate from an unconfined to a confined aquifer through the aquitard between them) and that the spatial variation of annual-average DGLR is a useful indicator of the relative probability of sinkhole development. In this study, a groundwater flow model using the MODFLOW computer code was developed and calibrated to simulate the spatial variation of annual-average DGLR to evaluate the relative probability of sinkhole development at an under-construction expressway and its vicinity. The results indicated that the expressway construction site has a relatively high probability of sinkhole development in the designed range of the pavement structures, and it is concluded that engineering action should be taken in advance to minimize potential sinkhole hazards.